WASTE MANAGEMENT SOCIALIZATION TO MAXIMIZE WASTE MANAGEMENT FOR CONVECTION BUSINESS - Emilia, Ni Kadek Ayu Kurnia; Putri, Putu Indah Dianti (LPPM Univ. Ibn Khaldun Bogor, 2023)
Socialization of waste management in the convection business will have a big impact on the business. The purpose of this research is to find out the urgency and relevance of waste management socialization in the context of a convective profession. The research method used is descriptive qualitative, using observation research techniques, interviews, and library studies and documentation. The results of this study reveal changes in the convection business culture, these changes include intensive education about the importance of waste management that has motivated businesses to take concrete steps to reduce waste and support sustainable practices. Deep understanding of the positive impact of these actions has created a new passion for work and a stronger foundation for sustainability.